RETRACTED: Neuroprotective Effect of Protein Phosphatase 2A/Tristetraprolin Following Subarachnoid Hemorrhage in Rats - Yin, Jian; Li, Ran; Liu, Wenchao; Chen, Yunchang; Zhang, Xin; Li, Xifeng; He, Xuying; Duan, Chuanzhi (Frontiers in Neuroscience, 2018)
Early brain injury (EBI) following subarachnoid hemorrhage (SAH) can lead to inflammation and neuronal dysfunction. There is a need for effective strategies to mitigate these effects and improve the outcome of patients who experience SAH. The mRNA-destabilizing protein tristetraprolin (TTP) is an anti-inflammatory factor that induces the decay of cytokine transcripts and has been implicated in diseases such as glioma. However, the mechanism of action of TTP in EBI after SAH is unclear. The present study investigated the effects of TTP regulation via phosphorylation in a rat model of SAH by protein phosphatase (PP)2A, which is a pleiotropic enzyme complex with multiple substrate phospho-proteins. We hypothesized that inhibitory phosphorylation of TTP by PP2A would reduce neuroinflammation and apoptosis. To evaluate the function of each factor, the PP2A agonist FTY720, short interfering (si)RNAs targeting TTP and PP2A were administered to rats by intracerebroventricular injection 24 h before SAH. Rats were evaluated with SAH grade, neurological score, brain water content and by western blotting, and terminal deoxynucleotidyltransferase dUTP nick-end labeling. We found that endogenous PP2A and TTP levels were increased after SAH. FTY720 induced PP2A activation would lead to dephosphorylation and activation of TTP and decreased production of tumor necrosis factor (TNF)-α, interleukin (IL)-6 and IL-8. SiRNA-mediated TTP knockdown abolished anti-inflammatory effects of FTY720 treatment, indicating that PP2A was associated with TTP activation in vivo. Decreased TNF-α, IL-6 and IL-8 levels were associated with improvement of neurological function, reduction of brain edema, suppression of caspase-3, and up-regulation of B cell lymphoma-2. These results demonstrated that PP2A activation could enhance the anti-inflammatory and anti-apoptotic effects of TTP, by which it might shed light on the development of an effective therapeutic strategy against EBI following SAH.